Insights into the role of gastrointestinal ultrasound in ulcerative colitis - Cristina Bezzio; Marta Vernero; Davide Giuseppe Ribaldone; Gianpiero Manes; Simone Saibeni (Therapeutic Advances in Gastroenterology, 2021)
Endoscopic evaluation with histological sampling is the gold standard for the diagnosis and follow-up of patients with inflammatory bowel disease (IBD), but in the past few years, gastrointestinal ultrasound (GIUS) has been gaining ground. Due to the transmural nature of inflammation in Crohn’s disease, GIUS has been mainly applied in this context. However, GIUS is now being reported to be accurate also for ulcerative colitis (UC). This review summarizes current knowledge on the use of GIUS in UC, with a focus on clinical practice. The review covers topics such as GIUS parameters, especially bowel wall thickness; the use of GIUS in assessing disease extent and in monitoring disease activity; GIUS indexes and scores; and the combination of GIUS with transperineal ultrasound for a better assessment of the rectum. With the always growing body of evidence supporting the accuracy of GIUS in UC, this diagnostic imaging modality can be expected to play a bigger role in disease flare evaluation, early treatment monitoring, and acute severe disease management.